1992
DOI: 10.1111/j.1432-1033.1992.tb17102.x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical trapping of a bacteriopheophytin anion in site‐specific reaction‐center mutants from the photosynthetic bacterium Rhodobacter sphaeroides

Abstract: The mutant YY in the reaction center of Rhodobacter sphaeroides, in which Phel81 on the L chain has been replaced by Tyr, and the double mutant FY, with Tyr210 on the M chain replaced by Phe and Phel81 on the L chain replaced by Tyr, have been constructed by site-directed mutagenesis. The studies described here were performed to complement a previous mutational analysis of mutant FF with Tyr210 replaced by Phe. Both new strains grow photoheterotrophically. The optical absorption spectra of reaction centers iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…This mutation should perturb the environment of the A side cofactors (including B A ), making electron transfer along the A-path less favorable and thus, allowing some B side electron transfer to take place. This suggestion is consistent with the results of Gray et al (1992) who used photopumping methods to generate a steady state population of bacteriopheophytin anion in a single site mutant of Rb. sphaeroides, M210(YfF) (a submutant of sym2-1).…”
Section: Effects Of Symmetry On the Rate And Yield Of Electronsupporting
confidence: 90%
“…This mutation should perturb the environment of the A side cofactors (including B A ), making electron transfer along the A-path less favorable and thus, allowing some B side electron transfer to take place. This suggestion is consistent with the results of Gray et al (1992) who used photopumping methods to generate a steady state population of bacteriopheophytin anion in a single site mutant of Rb. sphaeroides, M210(YfF) (a submutant of sym2-1).…”
Section: Effects Of Symmetry On the Rate And Yield Of Electronsupporting
confidence: 90%
“…1). The discrete asymmetry that the side chains of these residues provide to the RC structure is conserved in all species of photosynthetic bacteria and has been shown to play a significant role in electron and energy transfer functions of the RC (38–50). The residue at the L181 or M208 site can have a significant effect on the redox potentials and absorption spectra of the cofactors with which it can interact—P, B or H (or all)—on its respective side of the RC (26,44,51).…”
Section: Discussionmentioning
confidence: 99%
“…At low temperature two discrete peaks can be resolved at approximately 545 nm (for the Qx of HL) and 535 nm (for the Qx of HM). The purified mutant reaction centres described in [26] which bore the change Tyr M210--)Phe and Tyr M210-~Leu both exhibited a redshift in the position of the 535 nm band of 2-3 nm, considerably increasing the overlap between the HL and HM Q, peaks [14]. However, in all cases our purified mutant reaction centres showed no alteration in the position of the HM Qx band relative to its position in the spectrum of the wild type, with well resolved peaks being observed at 533 nm and 545 nm for the wild type and at 533 and 546 nm in the Tyr M210~Leu and Tyr M210~Phe mutants.…”
Section: Low Temperature Absorption Spectroscopy Andmentioning
confidence: 98%
“…sphaeroides which targetted the M210 residue found that replacement of the tyrosine increased the time constant for the reduction of H, from 3.5 ps to 16 ps and 22 ps for changes to Phe and Leu respectively [12], and to 10.5 ps and 16 ps for changes to Phe and Ile [13]. Recently it has also been reported that in reaction centres where the tyrosine at this position has been replaced by a phenylalanine, electron transfer to the Bphe on the inactive branch (H& can be observed under conditions where this does not occur in wild type centres [14], and experiments with mutants at the M2lO/Ll81 positions have also contributed to the proposal that during primary electron transfer the intermediate state P+BM-may be formed [15]. In the latter case the mutations appeared to modulate both the rate and extent of formation of this 'parking state' on the inactive branch.…”
Section: Introductionmentioning
confidence: 97%